Thermal Degradation and Fire Properties of Fungal Mycelium and Mycelium - Biomass Composite Materials. Issue 1 (December 2018) - Jones, Mitchell; Bhat, Tanmay; Kandare, Everson; Thomas, Ananya; Joseph, Paul; Dekiwadia, Chaitali; Yuen, Richard; John, Sabu; Ma, Jun; Wang, Chun-Hui
Abstract Mycelium and mycelium-biomass composites are emerging as new sustainable materials with useful flame-retardant potentials. Here we report a detailed characterisation of the thermal degradation and fire properties of fungal mycelium and mycelium-biomass composites. Measurements and analyses are carried out on key parameters such as decomposition temperatures, residual char, and gases evolved during pyrolysis. Pyrolysis flow combustion calorimetry (PCFC) evaluations reveal that the corresponding combustion propensity of mycelium is significantly lower compared to poly(methyl methacrylate) (PMMA) and polylactic acid (PLA), indicating that they are noticeably less prone to ignition and flaming combustion, and therefore safer to use. The hyphal diameters of mycelium decrease following pyrolysis. Cone calorimetry testing results show that the presence of mycelium has a positive influence on the fire reaction properties of wheat grains. This improvement is attributable to the relatively higher charring tendency of mycelium compared to wheat grain, which reduces the heat release rate (HRR) by acting as a thermal insulator and by limiting the supply of combustible gases to the flame front. The mycelium growth time has been found to yield no significant improvements in the fire properties of mycelium-wheat grain composites.